Analisis dan Perancangan Arsitektur Electronic Learning Systems (ELS) Amikom Purwokerto Menggunakan TOGAF untuk Meningkatkan Kualitas Pembelajaran Daring - Tarwoto; Ariska Nurul Habibah; Feishal Azriel Arya Putra; Asha Nuril Jannah; Epa Latifah; Ika Komalasari (Department of Informatics Engineering, Faculty of Computer Science, University of Kuningan, Indonesia, 2024)
The Electronic Learning System (ELS) is an online learning platform designed to facilitate access to course materials and manage the teaching-learning process more efficiently. Universitas Amikom Purwokerto has implemented ELS to support online learning. However, users face technical challenges, such as bugs during task uploads, lack of notifications for new assignments, and inefficient access, where course materials can be accessed without login authentication, potentially compromising security levels and threatening user data privacy. This study aims to analyze the implementation of ELS at Universitas Amikom Purwokerto using the TOGAF (The Open Group Architecture Framework) to identify system deficiencies and design corrective solutions. The method used is the Architecture Development Method (ADM) from TOGAF, covering the design stages through to the enterprise architecture development of the Electronic Learning System (ELS) information system. The study results indicate that enhancing the ELS architecture in terms of notification integration, system stability, and access efficiency can significantly improve the quality of online learning, providing a more optimal online learning experience for lecturers and students at Universitas Amikom Purwokerto.